NOT WITHOUT US. - Weizenbaum, Joseph (ETC: A Review of General Semantics)
Highlights the importance of computer professionals in the development of weapon systems. Power of computer professionals to alter the state of the world; Simulation of the imagination and creativity of technically oriented workers by many of the technical tasks and problems concerning artificial intelligence; Background on the Draper Laboratory, an institution devoted to missile guidance and submarine navigation.